REPRESENTASI PESAN MORAL DALAM FILM RUDY HABIBIE KARYA HANUNG BRAMANTYO (ANALISIS SEMIOTIKA ROLAND BARTHES) - Bagus Fahmi Weisarkurnai; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The research entitled moral representation in the movie hanung bramantyo habibie rudy the works (analysis of semiotic roland barthes). The story of the film in the true story of young man named baharudin jusuf habibie who tried to create an aircraft as well as build the aerospace industry indonesia. Inu research aims to find out how the moral messages in the film rudy habibie presented which then generate moral as human relationships with humans, the relationship of man with god, as well as human relationships the social environment.This study uses qualitative methods, with Roland Barthes semiotics analysis approach, taking a subject that is focused upon the character rudy. With views through faceted Denoted (signifier) describes the relationship of signifier and signified on reality, meaning explicit. Connotation (signified) describes the relationship of signifier and signified to non-reality, generate an implicit meaning and myth (the myth) explained the habits and beliefs prevailing in the society. In this study the scene is divided into 3 parts namely the relationship of man with man, the human relationship with the social environment with 11 scene data analysis unit. Data collection with the corpus contained in the film in accordance with the categorization of the already determined.The results of this research show that the representation of the moral messages in the film rudy this is habibie. First, look at human relationships with humans. Second, look at the relationship of man with god. Third, look at human relationships with the people in the social environment.Keywords : Film Rudy Habibie, Moral Message, Mass Communication, Semiotics